2015
DOI: 10.1089/ars.2014.5909
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-30 Family Inhibition Protects Against Cardiac Ischemic Injury by Regulating Cystathionine-γ-Lyase Expression

Abstract: Aims: Myocardial infarction (MI) is a leading cause of death globally. MicroRNAs (miRNAs) have been identified as a novel class of MI injury regulators. Hydrogen sulfide (H 2 S) is a gaseous signaling molecule that regulates cardiovascular function. The purpose of this study was to explore the role of the miR-30 family in protecting against MI injury by regulating H 2 S production. Results: The expression of miR-30 family was upregulated in the murine MI model as well as in the primary cardiomyocyte hypoxic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 46 publications
2
71
2
Order By: Relevance
“…In the field of cardiac research, research on the miR-30 family is mainly focused on myocardial hypertrophy, myocardial infarction, heart failure and ischemia reperfusion injury [27-29]. The miR-30 family also plays an important role in the inhibition of cardiac ischemic injury [30]. The results of this study showed that mi-30e-3p expression is significantly decreased after CME, meanwhile, myocardial autophagy is dramatically inhibited.…”
Section: Discussionmentioning
confidence: 90%
“…In the field of cardiac research, research on the miR-30 family is mainly focused on myocardial hypertrophy, myocardial infarction, heart failure and ischemia reperfusion injury [27-29]. The miR-30 family also plays an important role in the inhibition of cardiac ischemic injury [30]. The results of this study showed that mi-30e-3p expression is significantly decreased after CME, meanwhile, myocardial autophagy is dramatically inhibited.…”
Section: Discussionmentioning
confidence: 90%
“…As one of the endogenous H 2 S synthases, CSE is critical for H 2 S homeostasis. Previous research by our group and other groups demonstrated that plasma H 2 S levels in CSE -/ -mice decreased by *50% compared with those in wild-type (WT) mice (17,44). Thus, we compared the hepatic Hamp response between WT and CSE -/ -mice.…”
Section: Innovationmentioning
confidence: 94%
“…Quantification of H 2 S concentration H 2 S determination was performed using the methylene blue method as described previously (44).…”
Section: Immunofluorescence Stainingmentioning
confidence: 99%
“…Other studies showed that miR-106b is an antiapoptosis regulator and inhibits p21 expression, while miR-15b controls anti-angiogenic activity, suggesting that these two miRs may be robust regulators of apoptosis or angiogenesis relevant in myocardial infarction (Liu et al, 2012). MiR-30b has been implicated in cardiovascular pathophysiology such as the angiotensin II-induced myocardial hypertrophy, myocardial matrix remodeling, sprouting angiogenesis, and Ang II-induced cardiomyocyte apoptosis (Shen et al, 2014). NFκB positively regulates the expression of miR-30b and Bcl-2 in Angiotensin II-induced cardiomyocytes apoptosis, therefore miR-30b is suspected to play a regulatory role in apoptotic pathways (Wei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%